THE USE OF ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF AN ORDERLY TRAFFIC EDUCATION POSTER FOR THE PESAWARAN POLICE BASED ON MOBILE WEB TO IMPROVE STUDENT LITERACY - Triyas Hastomo; Tuti Puspitasari (IJISCS (International Journal of Information System and Computer Science), 2026)
Students' awareness of traffic discipline remains relatively low, as indicated by the high rate of violations and accidents among school-aged individuals. Conventional educational methods are considered less effective in engaging students in the digital era. The research problem focuses on how to develop a technology-based learning media that can enhance students’ understanding and engagement in traffic regulations. This study aims to develop and implement an Artificial Intelligence (AI)-based traffic education application that is interactive, adaptive, and user-friendly for high school students. This research employs the Research and Development (R&D) method, including stages of needs analysis, system design, mobile application development, AI implementation, and user testing. System evaluation was conducted involving 48 student respondents using a Likert-scale questionnaire covering interface, system security, and usability aspects. The results indicate that the application achieved a success rate of 86.00%, categorized as very successful. The usability aspect obtained the highest score of 88.50%, followed by interface (86.50%) and system security (83.00%). These findings demonstrate that the application effectively improves students’ understanding, enhances interactive learning experiences, and is easy to use. Therefore, the application is considered feasible as an AI-based educational tool to improve traffic safety literacy among high school students.